Overcoming mass-transfer limitations in partial hydrogenation of soybean oil using metal decorated polymeric membranes - Singh, D.; Pfromm, Peter H.; Rezac, Mary E. (My University, 2010)
The conventional soybean oil hydrogenation process (metal catalyst on solid support particles slurried in oil, H2 bubbled through the oil) is compared to metal-decorated integral-asymmetric polyetherimide (PEI) membranes, as far as changes in temperature and pressure are concerned. Using metal decorated-polymeric membranes, H2 is supplied to the catalytic sites by permeation from the membrane substructure. As opposed to the slurry process, metal-decorated membranes show only slightly increased trans fatty acid (TFA) formation when the temperature is raised (50-90°C) to accelerate the process. This is likely due to the efficient and to some extent self-regulating H2 supply directly to the catalytic sites on the membrane skin. The hydrogenation rate and TFA formation of the metal decorated membrane process show a minor dependence on pressure.